Massive reshaping of genome–nuclear lamina interactions during oncogene-induced senescence - Lenain, Christelle; de Graaf, Carolyn A.; Pagie, Ludo; Visser, Nils L.; de Haas, Marcel; de Vries, Sandra S.; Peric-Hupkes, Daniel; van Steensel, Bas; Peeper, Daniel S. (Genome Research, 2017)
Cellular senescence is a mechanism that virtually irreversibly suppresses the proliferative capacity of cells in response to various stress signals. This includes the expression of activated oncogenes, which causes Oncogene-Induced Senescence (OIS). A body of evidence points to the involvement in OIS of chromatin reorganization, including the formation of senescence-associated heterochromatic foci (SAHF). The nuclear lamina (NL) is an important contributor to genome organization and has been implicated in cellular senescence and organismal aging. It interacts with multiple regions of the genome called lamina-associated domains (LADs). Some LADs are cell-type specific, whereas others are conserved between cell types and are referred to as constitutive LADs (cLADs). Here, we used DamID to investigate the changes in genome–NL interactions in a model of OIS triggered by the expression of the common BRAFV600E oncogene. We found that OIS cells lose most of their cLADS, suggesting the loss of a specific mechanism that targets cLADs to the NL. In addition, multiple genes relocated to the NL. Unexpectedly, they were not repressed, implying the abrogation of the repressive activity of the NL during OIS. Finally, OIS cells displayed an increased association of telomeres with the NL. Our study reveals that senescent cells acquire a new type of LAD organization and suggests the existence of as yet unknown mechanisms that tether cLADs to the NL and repress gene expression at the NL.
10.1101/gr.225763.117